An all-arthroscopic light bulb technique to treat osteonecrosis of the femoral head through outside-in fashion without distraction: A case report - Xiong, Hua-zhang; Deng, Yu-hong; Jin, Ying; Wang, An-hong; Hong, Song (Frontiers in Surgery, 2022)
The distraction has been widely used in hip arthroscopy for opening the joint spaces. However, all-arthroscopic light bulb technique through outside-in fashion without distraction has not been reported for treatment of osteonecrosis of the femoral head (ONFH). A 29-year-old man was admitted to our department with hip pain and limited range of motion (ROM) in both hips over 4 months. X-rays, Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) showed a mixed appearance, including sclerosis and cysts on anterosuperior site of the bilateral femoral heads. The patient had an 11-year history of liquor intake. Additionally, no any other pathologies were found before operation. After diagnosing bilateral ONFH (stage II) according to the Ficat classification, the patient underwent all-arthroscopic light bulb technique through outside-in fashion without distraction because of failing conservative treatment. At the 2-year postoperative follow-up, the patient had neither pain nor limitation of ROM. The postoperative X-ray, CT and MRI revealed a well-healed area of the previous bone grafting in the bilateral femoral heads. All-arthroscopic light bulb technique through outside-in fashion without distraction can be a feasible method for treatment of early-stage ONFH. This case reminds us that the distraction and perforation-related complications may be avoided in patients with ONFH without the concomitant pathologies of the central compartment.